Multidrug-Resistant (MDR) Klebsiella variicola Strains Isolated in a Brazilian Hospital Belong to New Clones - Campos, Tatiana Amabile de; Almeida, Felipe Marques de; Almeida, Ana Paula Cardoso de; Nakamura-Silva, Rafael; Oliveira-Silva, Mariana; Sousa, Isabela Felix Alencar de; Cerdeira, Louise; Lincopan, Nilton; Pappas, Georgios Joannis; Pitondo-Silva, André (Frontiers in Microbiology, 2021)
Klebsiella variicola is mainly associated with opportunistic infections and frequently identified as Klebsiella pneumoniae. This misidentification implies a wrong epidemiology result as well as incorrect attribution to K. pneumoniae as the etiology of some severe infections. Recently, huge efforts have been made to study K. variicola, however, the biological aspects of this species are still unclear. Here we characterized five K. variicola strains initially identified as K. pneumoniae, with a Vitek-2 System and 16S rRNA sequencing. One-step multiplex polymerase chain reaction and Whole Genome Sequencing (WGS) identified them as K. variicola. Additionally, WGS analysis showed that all the strains are closely related with K. variicola genomes, forming a clustered group, apart from K. pneumoniae and K. quasipneumoniae. Multilocus sequence typing analysis showed four different sequence types (STs) among the strains and for two of them (Kv97 and Kv104) the same ST was assigned. All strains were multidrug-resistant (MDR) and three showed virulence phenotypes including invasion capacity to epithelial cells, and survival in human blood and serum. These results showed the emergence of new K. variicola clones with pathogenic potential to colonize and cause infection in different tissues. These characteristics associated with MDR strains raise great concern for human health.